MIGHTi: a sustainable mushroom pasteurization system for remote and off-grid communities - Thomason, Emily, author; Mizia, John, advisor; Sly, Brittney, committee member (Colorado State University. Libraries, 2026)
Mushroom cultivation requires effective substrate pasteurization to eliminate competing organisms while preserving beneficial microorganisms, yet conventional methods such as autoclaves and large-scale thermal systems are often resource-intensive and impractical for off-grid or rural environments. In regions such as rural Zambia, where access to consistent electricity is limited, there is a need for energy-efficient and accessible pasteurization solutions to support food production and improve diet diversity. Organizations such as MIGHTi are working to address these challenges by developing agricultural systems that can operate in resource-limited settings. The purpose of this project is to design and evaluate a mushroom substrate pasteurization system that can operate using off-grid solar power while maintaining effective temperature control and ease of use. This project investigates how a hybrid pasteurization method can meet the required thermal conditions while reducing water and energy consumption. The system was developed through an integrated engineering design approach combining mechanical, electrical, and control system components. The design includes a stainless steel tank housed within a plastic drum, substrate baskets, and a microcontroller-based user interface. A submerged heating element is used to heat water and generate vapor. There are thermocouples that monitor both substrate and water temperatures to ensure proper operation and provide safety shutdown in the event of overheating or low water conditions. The system is designed to maintain substrate temperatures between 60–70°C for durations ranging from 30 minutes to 2 hours, depending on substrate type. The final design demonstrates that a hybrid thermal approach can effectively achieve pasteurization conditions while reducing water usage and enabling compatibility with solar-powered operation. The integration of automated controls and safety features improves system reliability and usability. This project contributes a practical and scalable solution for mushroom cultivation in off-grid environments, supporting increased food accessibility, improved agricultural practices, and sustainable technology implementation in resource-limited communities.
Keywords: pasteurization; engineering; mushroom substrate